Significant Improvement in Magnetorheological Performance by Controlling Micron Interspaces with High Permeability Submicron Particles - Tianxiang Du; Ning Ma; Zenghui Zhao; Yitong Liu; Xufeng Dong; Hao Huang (Advanced Science)
Abstract The shear yield strength, sedimentation stability and zero‐field viscosity of magnetorheological fluids (MRFs) are crucial for practical vibration damping applications, yet achieving a balanced combination of these performances remains challenging. Developing MRFs with excellent comprehensive performance is key to advancing smart vibration damping technologies further. Theoretically, incorporating a multiscale particle system and leveraging synergistic effects between their can somewhat enhance MRFs’ performance. However, this approach often faces issues such as insignificant increases in shear yield strength and excessive rise in zero‐field viscosity. In response, this study employs a DC arc plasma method to synthesize a high magnetic permeability, low coercivity submicron FeNi particles, and further develops a novel CIPs‐FeNi bidisperse MRFs. The introduction of submicron FeNi particles not only significantly enhances the shear2019 yield strength of MRFs under low magnetic fields but also promotes improvements in sedimentation stability and redispersibility without excessively increasing viscosity. Comprehensive performance analysis is conducted to explore the optimal content ratio, and detailed mechanisms for the enhancement of performance are elucidated through analysis of parameters such as chain‐like structure, magnetic flux density and friction coefficient. Most importantly, the superior comprehensive performance combined with straightforward fabrication methods significantly enhances the engineering applicability of the CIPs‐FeNi bidisperse MRFs.